The making of an innovative multinational firm: Chinese capability development through the acquisition of MG-Rover - Simon Collinson (University of Birmingham, Birmingham Business School, 2013)
This paper examines the transfer, replication and adaption of knowledge, assets and capabilities in MG Rover from the British workforce to the new Chinese owners and employees at Nanjing Automotive Corporation (NAC). The study explores the intra-organisational processes adopted to integrate knowledge, innovation-related routines and networks. We identify distinctive mechanisms for both 'discrete' transfers and 'cumulative' flows of knowledge and capabilities, with different kinds of impact on the innovative capacity of the recipient firm. With the more recent take-over of NAC by SAIC the MG-NAC restructuring is examined as part of the broader evolution of a large, innovative and multinational Chinese car firm. The study also provides insights into the changing complementarities between Western and Chinese manufacturers and lessons for managers regarding effective alignment with evolving competitors.
Keywords: 650; take-overs; inter-organisational processes; knowledge flows